Architectural detailing : function, constructibility, aesthetics - Allen, Edward; Rand, Patrick (2016)
"Reviews recent built works and extract underlying principles that can be the basis for new patterns or for additional aspects of existing patterns"--
Includes index.
Keywords: Architecture -- Details; ARCHITECTURE / Design, Drafting, Drawing & Presentation